Perbaikan Sistem Hukum Dalam Pembangunan Hukum Di Indonesia - Azmi Fendri (Fakultas Hukum Universitas Riau, 2011)
Since reform marked by fall downing regime him Governance of New Order, peeping out a period to transition in course of democracy. Word democratize likely become tidy political jargon in the form of social issues and HAM which later then diekspos to society to oppose all policy of governance. Proper confessed during governance of New Order, democracy likely become very matter of taboo to be talked openly public. This matter of mirror from various legislation product which do not express justice of society in general.